Long-term impacts of nitrogen fertilization and straw incorporation on rice production and nitrogen recovery efficiency under plastic film mulching cultivation. (20th January 2021) - Sun, Yan; Zhu, Mengjie; Mi, Wenhai; Wu, Lianghuan
Abstract: The application of nitrogen (N) fertilizer as base fertilizer in plastic film mulching cultivation (PFMC) system easily leads to soil N deficiency in the late growth period of rice. The combination of N fertilization and straw incorporation was put forward and their impacts on rice yield and grain N recovery efficiency (NRE) based on a long-term experiment in a PFMC system were evaluated. Five N application levels included 0, 45, 90, 135, and 180 kg ha −1 and two subplots were rice straw removal (RSR) and rice straw incorporation (RSI). Moreover, RSR and RSI in a conventional flooding cultivation (CFC) system with 135 kg ha −1  N application rate were also included. The results showed that the optimum N application rate was 135 kg ha −1 . At this N application level, the promotion effect on yield and grain N uptake over years in PFMC system was more obvious than that in CFC system. Continuous PFMC might accelerate the mineralization of soil organic matter and the increase of soil N availability. However, RSI had no obvious promotion effect on the increment of yield, grain NRE, and soil available N with years compared with RSR in PFMC system. In conclusion, film mulching with the N fertilizer application rate of 135 kg ha −1 improved soil thermal condition in early growth stage of rice, and thus enhanced the availability of soil N, grain N uptake, and yield. This provides a reference for PFMC application in water-saving rice production system.